Laboratory and computer simulations of reinforced concrete frames with different ductility. (20th April 2016) - Galanis, Panagiotis; Shin, Yoon Bong; Moehle, Jack P.
Summary: Reinforced concrete structures that lack proper seismic detailing commonly have increased vulnerability to collapse during strong earthquake shaking. A major contributor to building collapse vulnerability is the prevalence of columns with widely spaced and poorly configured transverse reinforcement. Such columns are susceptible to shear failures, which can lead to axial failures and local or global building collapse. This study presents a laboratory test program that was designed to gain insight into the effects of column detailing on the dynamic response including collapse of concrete frames. Twelve concrete frames were tested on a shaking table and were subjected to two types of ground motions: one relatively short‐duration motion with strong velocity pulse and one relatively long‐duration motion with multiple cycles. The study also evaluates the effectiveness of modern analytical methods to simulate the nonlinear dynamic response of concrete structures. Two lumped plasticity models employing nonlinear rotational and shear springs at the column ends were used to simulate the collapse response of the tested specimens. The study demonstrates that modern analytical techniques can simulate reliably the nonlinear dynamic response of concrete structures in the post‐yielding stage and can identify the onset of shear failure and collapse of concrete frames. However, in the majority of cases, the analytical models overestimated the effects of damage accumulation, especially for long‐duration motions. Response predictions were improved by adjusting the damage modeling parameters. Copyright © 2016 John Wiley & Sons, Ltd.